Tożsamość homoseksualnych kobiet – dramat czy konstruktywna alternatywa? - Wierzba, Paulina (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article Identity of Homosexual Women – Drama or a Constructive Alternative? presents the most important aspects of homosexual identity changes, which can be observed in modern society, especially as far as problems of homosexual women are concerned. The main goal of this article is to show the crash of modernism and postmodernism ideologies connected to cultural pluralism and axiological relativism and their consequences for the shape of lesbian’s identity. Reflections are illustrated by the statements from the homosexual women’s websites. As a result, main issues can be understood better